2013
DOI: 10.1021/jo4001433
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Free Radical Autoxidation: The Physical Organic Chemistry of Polyunsaturated Fatty Acid and Sterol Peroxidation

Abstract: This Perspective describes advances from the author’s laboratory on the free radical reactions of organic compounds with molecular oxygen. Polyunsaturated fatty acids (PUFAs) and sterols are particularly prone to undergo radical chain oxidation and evidence suggests that this process, known as lipid peroxidation, occurs in vivo under a variety of conditions that are the result of an oxidative stress. Cyclic peroxides, hydroperoxides, and epoxy-alcohols are major products formed from peroxidation and the basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 129 publications
(265 reference statements)
0
78
0
Order By: Relevance
“…The level of MDA production in each exposure group was quantified according to the specific absorbance of adducts at 532 nm. 22 8-Oxoguanine determination using liquid chromatography-mass spectrometry/mass spectrometry (lc-Ms/Ms)…”
Section: Mda Generation In E Colimentioning
confidence: 99%
See 1 more Smart Citation
“…The level of MDA production in each exposure group was quantified according to the specific absorbance of adducts at 532 nm. 22 8-Oxoguanine determination using liquid chromatography-mass spectrometry/mass spectrometry (lc-Ms/Ms)…”
Section: Mda Generation In E Colimentioning
confidence: 99%
“…The peroxidation of lipid by active free oxidative radicals could produce oxidized products of aldehydes, such as MDA and 4-hydroxyl nonenal (4-NHE), resulting in the loss of cell membrane integrity and even damage on cell structure. 22,40 MDA, as a common biomarker, was quantitatively measured in E. coli treated with Cit@AgNPs and Ag + to evaluate the potential lipid peroxidation. The results in Figure 5A show that Cit@AgNPs and Ag + treatments slightly increase MDA levels in E. coli, indicating the existence of lipid peroxidation due to oxidative damage.…”
mentioning
confidence: 99%
“…The bis-allylic methylene group of polyunsaturated lipids is particularly vulnerable to radical attack, [13][14][15] and a recent strategy to diminish lipid peroxidation in vivo is based on deuterium substitution at the reactive center. 16 Incubation of yeast with small amounts of 11,11-D 2 linoleic acid (11,11-D 2 -Lin), for example, increases the resistance of yeast to oxidative stress, 17 and the same isotopically reinforced fatty acid diminishes neurodegeneration in a mouse model of Parkinson's disease.…”
mentioning
confidence: 99%
“…reported that 7-dehydrocholesterol is the most oxidizable lipid molecule, and that the consequences of its extreme reactivity on human health should be clarified 20,21 .…”
Section: Enzymatic and Non-enzymatic Lipid Peroxidationmentioning
confidence: 99%